Meropenem in combination with baicalein exhibits synergism against extensively drug resistant and pan-drug-resistant Acinetobacter baumannii clinical isolates in vitro - Guran, Mumtaz; Cakiral, Kadir; Terali, Kerem; Kandemir, Tulay; Sanliturk, Gizem; Ocal, Melda Meral; Koksal, Fatih (Oxford Univ Press, 2023)
Several studies have demonstrated that the effectiveness of carbapenems against drug-resistant Acinetobacter baumannii infections has been decreasing. Combination therapy with two or more drugs is currently under investigation to overcome the emerging resistance against carbapenems. In this study, we tested the possible synergistic interactions of a potent antibacterial flavonoid, baicalein, with meropenem to illustrate this duo's antibacterial and antibiofilm effects on 15 extensively drug resistant or pan-drug-resistant (XDR/PDR) A. baumannii clinical isolates in vitro. Isolates included in the study were identified with MALDI-TOF MS, and antibiotic resistance patterns were studied according to EUCAST protocols. Carbapenem resistance was confirmed with the modified Hodge test, and resistance genes were also analyzed with genotypical methods. Then, checkerboard and time-kill assays were performed to analyze antibacterial synergism. Additionally, a biofilm inhibition assay was performed for screening the antibiofilm activity. To provide structural and mechanistic insights into baicalein action, protein-ligand docking, and interaction profiling calculations were conducted. Our study shed light on the remarkable potential of the baicalein-meropenem combination, since either synergistic or additive antibacterial activity was observed against every XDR/PDR A. baumannii strain in question. Furthermore, the baicalein-meropenem combination displayed significantly better antibiofilm activity in contrast to standalone use. In silico studies predicted that these positive effects arose from inhibition by baicalein of A. baumannii beta-lactamases and/or penicillin-binding proteins. Overall, our findings highlight the prospective potential benefits of baicalein in combination with meropenem for the treatment of carbapenem-resistant A. baumannii infections. Remarkable therapeutic potential of meropenem-baicalein combination is presented in this in vitro study.
Keywords: Acinetobacter baumannii; baicalein; carbapenem; synergy